Usability evaluation of DEAF mobile application interface: A systematic review - Nathan, Shelena Soosay (Medwell Publishing, 2018)
Mobile applications for deaf is getting popularity but lacking in evaluating the usability of these applications. Existing models to evaluate mobile applications is very general to be applied in identifying usability problem for the special need people. This study investigates few important dimensions to be applied in developing a usability evaluation model for mobile applications for deaf specifically. Systematic Literature Review (SLR) is used in achieving this objective with identification of dimensions that support usability model development.A total of 515 papers were downloaded and has been narrowed down into 44 articles that finally selected for the study. The results show that the most usability dimensions appear in the articles are effectiveness, efficiency, learnability, accessibility and satisfaction which contribute towards measuring the usefulness of mobile application meant to the deaf community.